The Contextual Essentiality of Mitochondrial Genes in Cancer - Thomas, Luke W.; Ashcroft, Margaret (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are key organelles in eukaryotic evolution that perform crucial roles as metabolic and cellular signaling hubs. Mitochondrial function and dysfunction are associated with a range of diseases, including cancer. Mitochondria support cancer cell proliferation through biosynthetic reactions, and their role in signaling, and can also promote tumourigenesis via processes such as oncometabolite production, and the production of reactive oxygen species (ROS). The advent of (nuclear) genome-wide CRISPR-Cas9 deletion screens has provided gene-level resolution of the requirement of nuclear-encoded mitochondrial genes (NEMGs) for cancer cell viability (essentiality). More recently, it has become apparent that this essentiality of NEMGs is highly dependent on the cancer cell context. In particular, key tumour microenvironmental factors such as hypoxia, and changes in nutrient (e.g. glucose) availability, significantly influence the essentiality of NEMGs. In this mini-review we will discuss recent advances in our understanding of the contribution of NEMGs to cancer from CRISPR-Cas9 deletion screens, and discuss emerging concepts surrounding the context-dependent nature of mitochondrial gene essentiality.